Comparison of the effectiveness of baits used in traps for adult fly collection - Boonchu N. (2014)
The effectiveness of 6 different baits used in fly traps for adult fly collection was compared in October-November, 2000, near the cafeteria of Maharaj Nakhon Chiang Mai Hospital, Chiang Mai Province, northern Thailand. The baits used were fresh viscera (pork, beef and fish) and fresh meat (pork, beef and fish), with 500 g of each kind being used in each fly trap for each experiment. All were replicated four times. Pork viscera yielded the highest effectiveness (35.2%), followed by fish meat (30%). Four other kinds of bait showed relatively low efficiency, ie fish viscera (12.0%), beef viscera (9.0%), pork meat (8.4%) and beef meat (5.4%). The calliphorid Chrysomya megacephala was the most abundant fly species collected, while sarcophagids and muscid flies were found in much smaller numbers. The number of females was higher than males in all collections. Although all baits used were parts of animal carcasses that were very attractive for adult flies to feed upon and oviposit, the result of this study showed the differences in their effectiveness for fly collection, particularly during the late rainy season to early winter in Chiang Mai. Pork viscera showed the highest efficacy for metallic fly collection, but not for all species. Further study of suitable baits for the medically important fly species that exist in urban areas should, therefore, be performed.